Docência universitária: ideações sobre a prática docente de professores atuantes em cursos de Publicidade e Propaganda - Pedrini, Igor Aparecido Dallaqua (2018)
The study of University Teaching (UT) in the Advertisin courses becomes necessary in a context in which technologies and economic dynamics transform the production and reception flows into the advertising and consumption system, putting the profession in state of changes. Studying the teaching profession of the advertising teacher is to participate in an effort that contributes to the improvement of the activity. This research, located in the Research Line of Educational Knowledge and Practices, presents as hypothesis, for this thesis, that advertising teachers practice their classroom practice through their experience in the labor market, without, however, worrying with an educational training. From the historical course of the teaching of advertising in the country, there is the existence of the paradigm of learning by practice, influencing still today the courses of Advertising. The problems that support this research is: 1º) What degree of importance do the university professors in Advertising course attribute to the categories of study: teaching knowledge, teaching and learning and evaluation? 2º) What ideations these teachers have about their pedagogical practice? The central objectives for this research are: "to study and analyze the degree of importance that the university professors in the course of Advertising attribute the categories: teaching knowledge, teaching and learning and evaluation; aiming to understand and describe the ideas that these teachers have about their pedagogical practice.” As a methodological contribution, within the quantitative and qualitative approaches, a research instrument was applied in three parts: I- Identification of the subjects; II - Categories of analysis: Teaching Knowledge, Teaching and Learning, Evaluation; III - consisting of three open questions, which belong to the last item of each category. They are: a) For you, what factors are able to improve your teaching practice even more ?; b) How do you facilitate the process of teaching and learning for your students?; c) For you, did the student learn when? The result showed that advertising teachers idealize their pedagogical practice from the techniques of the labor market, seeking a balance with pedagogical knowledge. Based on the finding that the briefing is the mediator between the professional practices and the classroom, five didactic-pedagogical techniques were suggested in which the advertising tool is associated with the expositive class, expository dialogues, technical visits, teaching with research and seminar, in order to contribute to the improvement of teaching practice of the advertising teacher.